Eco enzyme mixture of sludge sediment treatment reduces BOD, COD, TSS, and detergent content in greywater - Hermiyanti, Pratiwi; Rokhmalia, Fitri; Ipmawati, Putri Arida; Amalia, Rizki (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Household activities generate greywater containing pollutants such as BOD, COD, TSS, and detergents, contributing to environmental pollution. Eco enzyme offers a biological alternative to degrade organic waste. Objective: This study aimed to evaluate the effectiveness of the eco enzyme combined with sludge sediment in reducing greywater pollutants. Methods: A true experimental study with a pretest–posttest control group design was conducted using four greywater reactors. Eco enzyme doses of 10 ml, 30 ml, and 50 ml per 1000 ml of wastewater were tested, along with a control. The eco enzyme was mixed with 1.5 liters of sludge sediment. The detention time was three days. Sampling was performed once per treatment using purposive sampling. Parameters analyzed included BOD, COD, TSS, and detergents based on SNI standards. Data were analyzed using one-way ANOVA. Results: The treatment showed no significant effect on BOD reduction (p=0.48), but significantly reduced COD (p=0.01) and TSS (p=0.0001). Detergent reduction was moderate, with the 50 ml dose being the most effective, although not statistically significant (p=0.07). Conclusion: Eco enzyme combined with sludge sediment has potential as a simple biological treatment to reduce COD, TSS, and detergents in greywater. However, additional processes such as aeration are needed to effectively reduce BOD. This research can be the basis for the development of advanced research that can apply eco enzymes to waste, with a longer time and more varied dosage use.